Factors predicting success of trial of labour after caesarean in current scenario - Singh, Pooja S.; Bamaniya, Jaishree; Shah, Ami (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Cesarean deliveries have been on the rise in recent decades, and as a result the question of how to manage subsequent deliveries becomes ever more important. The National Institute for Health and Care Excellence, RCOG, American College of Obstetricians and Gynecologists, and National Institutes of Health are in consensus that planned VBAC is a clinically safe choice for the majority of women with a single previous lower segment caesarean delivery, the authors explain. Aim of the study was to identify potential predictors of successful VBAC and study the risk and benefits involved. Methods: This was a prospective study in GCS Medical College. Seventy five cases were chosen fulfilling the eligibility criteria and were subjected to study. Results: The outcome was measured as successful VBAC. Out of 75 cases included in our study, 43 cases (57.3% of total cases) qualified for TOLAC during labour. Successful TOL (trial of labor) was observed in 48.8 % (21 out of 43) resulting in VBAC (vaginal birth after caesarean) and the rest 51.2% of failed TOL ended in repeat caesarean delivery. Conclusions: In our study, most of the women with successful VBAC were less than 30 years of age (95.2%). In our study, successful VBAC cases (90.5% of cases) presented with cervical dilatation more than equal to 4 cm and most cases (95.2%) of VBAC delivered before 38 weeks of gestation. Out of all VBAC’s, 62% (13 out of 21) had ante natal indication for their previous caesarean delivery; most common indication being breech. In our study, Repeat C.S. in failed TOL was performed for scar dehiscence in 41% cases.